Percepção do transporte não motorizado (bicicletas) no município de Vitória-ES - Leão, Rose Mary Nunes (2016)
The use of bicycles has been presented as a viable alternative to minimize urban mobility problems in cities. However, the poor infrastructure still poses a drawback to the movement of cyclists on the cities roads, often shared with other modes of transport. This dissertation aims to verify if the mobility plans attend the cyclists in the city of Vitória, considering answers from surveys conducted in the years 2012 and 2015. The analysis consists in the identification of the cyclists profile, their journey patterns. Also this study intent to know the theoretical and historical aspects about the cycling paths network´s planning, considering the particular aspects of its space. Descriptive statistics and simple data comparisons were performed by using vehicle counting and cyclists interview. Cartographic products were built identifying origin, destination and place of residence of cyclists. These products allowed a spatial understanding of their journey patterns. Official plans were analyzed, and compared with the 2012 and 2015 survey data.The respondents stated that there are flaws in the actions of the implemented plans and mobility programs carried out by the local government. Among the many problems identified are the lack of implementation of more cycle roads, the absence of connections between most of them, the lack of security and the disrespect of drivers towards cyclists Data of both surveys 2012 and 2015 showed the same results for the cyclist profile. The majority is male, age in the range of 21 and 50 years old, employed, and the bike is mainly used for economic reasons.Statistical difference in the question about the reason for using bicycles in the two periods of research was verified. In 2012, the reason for riding a bicycle was to work and, in 2015, responses were divided between for work and leisure. It was found that between 2012 and 2015 the number of cyclists who had cars has increased. In 2015, the cyclists who were interviewed reported that they used bike mostly to go to work. Interventions in mobility plans such as construction and signaling bike roads may have contributed to this change in attitude.